Accounting for the impact of genotype and environment on variation in leaf respiration of wheat in Mexico and Australia - Gaju, Oorbessy; Bloomfield, Keith J.; Negrini, Anna C.A.; Bowerman, Andrew; Cullerne, Darren; Posch, Bradley Cooper; Bryant, Callum J.; Fan, Yuzhen; Spence, Matthew A.; Stone, Bethany; Gilliham, Matthew; Furbank, Robert; et al. (Oxford University Press, 2025)
An approach to improving radiation use efficiency (RUE) in wheat is to screen for variability in rates of leaf respiration in darkness (R dark). We used a high-throughput system to quantify variation in R dark among a diverse range of spring wheat genotypes (301 lines) grown in two countries (Mexico and Australia) and two seasons (2017 and 2018), and in doing so quantify the relative importance of genotype (G) and environment (E) in influencing variations in leaf R dark. Through careful design, residual (unexplained) variation represented <10% of the total observed. Up to a third of the variation in R dark (and related traits) was under genetic control. This suggests opportunities for breeders to use R dark as a novel selection tool. In addition, E accounted for more than half of the total variation in area-based rates of R dark. Here, the day of measurement was crucial, suggesting that day-to-day variations in the environment influence rates of R dark measured at a common temperature. Overall, this study provides new insights into the role G and E play in determining variation in rates of leaf R dark of one of the most important cereal crops, with implications for future improvements in carbon use efficiency and yield.